Adaptive Control in Passive rehabilitation routines using ELLTIO - López-Gutiérrez, R.; Aguilar-Sierra, H.; Lozano, R. (Revista Mexicana de Ingenieria Biomedica, 2017)
The Exoskeleton for Lower Limb Training with Instrumented Orthosis (ELLTIO) is a mechatronic device that can be used to assist in passive kinesitherapy to increase human muscles strength and resistance (1). This paper presents an alternative for passive rehabilitation process using an exoskeleton for knee and ankle. The main idea is assist a professional physiotherapist in the design and performance of exercises routines for his patients using the prototype. The knee and ankle joint’s movements are recorded and storage during the exercises to propose a similar computer generated trajectories which the exoskeleton on should follow. An adaptive controller is implemented to track the trajectories and adapt the user parameters.